The National Forest Cover Monitoring Using Satellite Imagery - Singh, Ashbindu (Indian Forester, 1986)
India's forests have been continuously declining in recent years due to a variety of reasons. The absence of virtually any reliable data base on the extent and rate of deforestation taking place in the country makes the establishment of a system of continuous operational monitoring of forest cover a necessity. The satellite technology has potential to form a basis for such a monitoring system at the national level.